CHALLENGES AND SOLUTIONS OF VALUE EDUCATION IN THE CURRENT SCHOOL CURRICULUM - Vasava, Dilipbhai Jaisingh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In this research paper I have described my topic “Challenges and solutions of implicit value education in initial school curriculum” as much as possible. Inherent value education is an important and necessary part of initial school curriculum, which aims to make students aware of social, mental and moral values. This education not only makes students aware of personal development, but also promotes their sensitivity towards social responsibilities and moral values. Its ideal objective is to make students understand the basic principles of empathy, cooperation and harmony so that they can make a positive contribution to the development of society. It helps them to understand the basic feeling of co-existence and harmony with all living beings. Under implicit value education, students are taught the basic principles of mindset, harmony and social service through live examples, stories and thoughts. Through this, students learn to live a life with moral values. They are able to achieve success and satisfaction in their lives and spread virtues in the society. Inculcating value education is an important part of the school curriculum which prepares students as aware, conscious and ethical citizens of the society. It guides them in the moral direction required to follow the right path in their personal and social life.